Study on Internet Marketing Practices of Tourism Industry by Travel Agency of Nepal (Pravaha, 2018)
Nepal is famous destination for international travelers through tour started only after sixties. Nepal within two decades became successful to have it significant position in world tourism scenario. Tourism in Nepal becomes a strong contributor in National economy after it boomed in eighties. It has become important foreign export being major source of foreign exchange. A part from this, it has been contributing in creating direct & indirect employment opportunities. Realizing the importance of tourism sector to uplift national economy, Nepal government has formulated various policies plan, and strategies to develop tourism as sustainable industry. Tourism master plan 1972 was an important step in policy formulation Nepal Tourism Board (NTB) was established in 1999 with the principle of Public Private Partnership (PPP) with the Principle of Public Private Partnership (PPP) approach. Since then, NTB has been marketing "Nepal as an enchanting holiday destination in world tourism market. It has adopted various strategies and undertaken different activities in order to promote Nepal as a must visit destination. We have abundant resources for which the country enjoys competitive advantages. Tourism represent one among such sectors which could rebuild the image of the country bringing back multifaceted benefit to the country and the people at large it also emerged as an exemplary model for the Nepalese economy and represent around 4% to the country GDP and is also a major source of employment, it has developed as an independent sector of the economy heavily involving the Nepalese private sector. Travel agencies are among such private sector wings which are responsible to bring or has contributed to great extent to invite lots of tourist from all over the world. So to great extent promotion of tourism by these travel agencies has direct correlation with the inflow of tourist in Nepal. In order to find the perception of travel agencies regarding internet marketing prospect practiced in tourism sector. Pravaha Vol. 24, No. 1, 2018, Page: 137-146